Polarized light fundamentals and applications - Collett, Edward (Optical engineering (Marcel Dekker, Inc.), 1993)
This self-study guide explores polarization using the Stokes vector, the Stokes parameters and the Mueller matrices - lending a modern perspective to the topic. It includes material on the experiment for the classical Zeeman effect. Facilitating the study of polarized light without prior knowledge of Maxwell's equations, this book: utilizes the classical wave theory of optics in place of Maxwell's equations wherever possible; shows polarized light in terms of observables (Stokes polarization parameters), linking theoretical descriptions of the optical field to quantities that are actually measured in the laboratory; examines in detail Maxwell's theory and its connection to polarized light, and to accelerating charges in classical electrodynamics and quantum mechanics; documents various measurement methods using the Stokes vector and Mueller matrices; and explores the characterization of the complex refractive index and film thickness of optical materials.